Somatotype of Korean combat sport athletes based on weight divisions - Woong, N.; Min, Y.; Hyun, K.; Uk, L.; Young, K.; Kyu, L.; Sun, P.; Deok, L.; Sub, S.; Ho, K.; Jung, K.; Ilhyun, K.; et al. (Archives of Budo, 2018)
Background and Study Aim: It is well established that somatotypes are defined by the physical characteristics of the body. However, the somatotype results of Korean combat sport athletes have not yet been established. The purpose of study was the somatotype of Korean combat sport athletes based on body weight divisions and physical characteristics in relations the practice of training and sport rehabilitation.